Penguatan Ekonomi Melalui Penggunaan Sistem Sosial Media Brand Produk Umkm Roti Samir di Desa Tegalrejo Kecamatan Pulung - Mukhamad Nasih; Mariana Mariana (Social Science Academic, 2023)
In Tegalrejo village, Tegalreejo hamlet, Pulung Ponorogo sub-district, there are samir bread MSME companies that need improvement in introducing their products to outsiders. Social media branding is branding activities through social media. Branding is not just about logos, taglines, value propositions, or other visual things. Branding is also an effort that businesses make to raise and develop a brand, besides that branding is also done in finding a place or location to carry out business activities. One of the popular branding methods today is branding using social media. Popular branding that is often used to develop SMEs brands in Indonesia by using the platforms Sopee, Lazada, Toko Pedia, and many other platforms that may be more efficient or often used by young people today, such as using social media accounts such as WhatsApp, Facebook, instagram, and tik tok,. Tiktok is one of the social media that is widely used as a branding media for online promotion of goods or services, usually the promotion of these goods and services is in the form of photos and videos. Tiktok is a new media that has developed very rapidly, compared to other media categories, such as Facebook, Instagram, YouTube and Twitter. New media presents digitization, convergence, interactivity, and development of network in conveying its messages. This study uses a qualitative method using a descriptive qualitative approach, in which the researcher describes and explains the situations and conditions that occurred in social media branding after the Cofid-19 outbreak. Descriptive research is research that contains data quotations to give an overview of the presentation. Research data can be obtained from interviews, notes, and photographs. Researchers use interviews with questions of why, what reasons and how. The location of this research is in the village of Tegalrejo, Pulung District, Ponorogo Regency. UMKM Samir bread was established in 2021 with the status of self-ownership in the village of Tegalrejo, Pulung sub-district. Micro, small and medium enterprises, Samir Roti MSME, which have been running for about 2 years and still use simple branding, Samir Roti MSME are still not optimal in marketing and strengthening the product brand, so researchers will introduce economic strengthening through media branding through the Tiktok social media account. In 2020-2023 the tiktok apk in Indonesia is very busy being used by the community, this can be an opportunity for small brands to introduce their products to a wider community. With digital marketing, it makes it easy for MSME business actors to promote their products and consumers easily when looking for a product. The goal of digital marketing is to connect consumers and also companies which can share information and communicate between producers and consumers. Digital marketing or branding activities can be carried out through several social media platforms that can be used including Instagram, Twitter, Facebook, Tiktok and others.